Determination of thermal conductivity of CFRP composite materials using unconventional laser flash technique. (August 2018) - Adamczyk, Wojciech P.; Pawlak, Sebastian; Ostrowski, Ziemowit
Highlights: Non-destructive technique for TC assessment of composite material. Development of unconventional measuring techniques for measuring TC of composite materials. Application of advance numerical model to predict heat transfer within body and heat losses into the surrounding. Application of optimization algorithm to retrieved TC/TD of composite material. Evaluated results have shown very good accuracy with standard Transient Thermography technique. Abstract: The purpose of the paper is to show an application of the inverse technique for measuring thermal conductivity (TC) of the carbon fiber reinforced polymer composites. In the proposed technique the heat energy source and IR detector are located at the same side of the investigated sample, which allows taking into account the finite dimension, as well as real shape of the sample. These were accounted for by application of the multidimensional mathematical model that allows simulating the spatial and temporal distribution of the heat within entire body. The non-destructive character of the measurement technic is highly demanded in industrial applications. The core of the mathematical algorithm used for retrieving TCs consists of the finite volume solver. Proposed methodology determines the TC of material by fitting the calculated spatial and temporal temperature field to the measured data. This paper also describes an original in-house apparatus, which was developed to carry out the present experimental trials.